The role of marketing in achieving change within Public business organizations - Tarouch, Faris (Milev Journal of Research and Studies, 2023)
This article aims to highlight the role of marketing in bringing about change to improve the work of business organizations, especially public organizations in algeria, for a long time these organizations have been a burden on the state, rather than achieving the desired economic objective of creating added value for itself and those around it, where should this situation be changed by the treatment and significantly the marketing function, which suffers great shortcomings in it, mainly due to philosophical and administrative backlogs and political backgrounds, which may achieve a comprehensive change of her policies and objectives and her market and social status, a situation that has been identified in a sample of public organizations and has proved the correctness of the change required.